A two-color interferometer for high-order harmonic generation - Pefani,Eleni (Lund Reports on Atomic Physics (LRAP), 2025)
High-order harmonic generation (HHG) is a highly nonlinear optical process in which extreme ultraviolet (XUV) radiation is generated due to the interaction of an intense laser field with atoms. This process enables the production of high harmonics, which would not be achieved with standard nonlinear media. The utilization of two-color laser fields (formed by combining a fundamental field with one of its harmonics) has revealed that the electron trajectories involved in the process can be manipulated, resulting in the enhancement of High Harmonic Generation yield and overall efficiency. In particular, combinations involving second or third harmonics with the fundamental field, have been shown to significantly enhance the High Harmonic Generation efficiency or selectively enhance the High Harmonic Generation flux of specific harmonics, by fine tuning of the relative phase and intensity ratio of the two fields. This thesis presents the design and construction of a setup based on an Ytterbium laser system, in which the generation of third harmonic was accomplished, with a 15% conversion efficiency. Initially, theoretical comparisons between direct third-harmonic generation (THG) and a cascaded approach, which is second-harmonic generation (SHG) followed by sum-frequency generation (SFG), indicated that the latter results in a higher conversion efficiency for third harmonic. Based on this result, an interferometric setup was implemented, and further limitations that could decrease the efficiency of Third Harmonic Generation were investigated. For instance, the impact of spatial and temporal walk-off, common limitations following the cascaded process, were analyzed to further optimize the system. Power scans were performed to identify the optimal intensity ratios between the second harmonic and residual IR fields, leading to maximized Third Harmonic Generation efficiency. The presented setup is an early version of a final system in which all three beams (fundamental, second harmonic, and third harmonic) will be an output with controllable relative powers. This is important for two-color High Harmonic Generation experiments where the flexibility to adjust the intensity ratio between the fields is needed. To study how waveform shaping, of the incident laser field, impacts High Harmonic Generation, simulations were performed based on the three-step model, using a combination of the fundamental and its third harmonic field. These simulations investigated the impact that the relative phase and intensity ratio of the two fields have upon the electron trajectories and resulting harmonic yield. The focus of the simulations was on identifying waveform configurations that lead to flatter return energy curves, which suggests that a large number of electrons are ‘forced’ to release the same kinetic energy, thus enhancing the yield at specific harmonic orders.
Keywords: Laser; Nonlinear Optics; High Harmonic Generation; Third Harmonic Generation; Interferometer; two-color HHG; Femtosecond